2018
DOI: 10.1111/bjdp.12233
|View full text |Cite
|
Sign up to set email alerts
|

Icon arrays help younger children's proportional reasoning

Abstract: We investigated the effects of two context variables, presentation format (icon arrays or numerical frequencies) and time limitation (limited or unlimited time), on the proportional reasoning abilities of children aged 7 and 10 years, as well as adults. Participants had to select, between two sets of tokens, the one that offered the highest likelihood of drawing a gold token, that is, the set of elements with the greater proportion of gold tokens. Results show that participants performed better in the unlimite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 108 publications
(137 reference statements)
0
16
0
Order By: Relevance
“…We further provide the first evidence that young children intuitively reason about ratios with symbolic numerals. While one previous study found that slightly older 7‐ to 10‐year‐old children could compare ratios presented as a frequency distribution (e.g., 4 tokens out of 10 are gold), the stimuli in that study were constructed such that children could have attended only to the numerator rather than truly evaluating the ratio of the numerator to the denominator (Ruggeri, Vagharchakian, & Xu, 2018). This study is thus the first to demonstrate that 6‐ to 8‐year‐old children can perform approximate ratio comparisons with a symbolic format without relying on unidimensional comparison heuristics.…”
Section: Discussionmentioning
confidence: 99%
“…We further provide the first evidence that young children intuitively reason about ratios with symbolic numerals. While one previous study found that slightly older 7‐ to 10‐year‐old children could compare ratios presented as a frequency distribution (e.g., 4 tokens out of 10 are gold), the stimuli in that study were constructed such that children could have attended only to the numerator rather than truly evaluating the ratio of the numerator to the denominator (Ruggeri, Vagharchakian, & Xu, 2018). This study is thus the first to demonstrate that 6‐ to 8‐year‐old children can perform approximate ratio comparisons with a symbolic format without relying on unidimensional comparison heuristics.…”
Section: Discussionmentioning
confidence: 99%
“…Ruggeri et al (2018) found positive correlations between the numerical and probabilistic reasoning abilities across age groups and within the youngest age group. Notably, Ruggeri et al (2018) only assessed children's ability to compare probabilities. In their literature review, Bryant and Nunes (2012) described probability as a complex concept for which we have to fall back on our understanding of different sub-concepts: randomness, sample space, quantification and comparison of probabilities, and correlation.…”
Section: Probabilistic Reasoning Abilities and Early Numerical Abilitiesmentioning
confidence: 81%
“…In binary choice tasks, participants have to choose the best of two sets, each containing desired and undesired elements, to blindly draw from (Falk et al, 2012). Ruggeri et al (2018) found positive correlations between the numerical and probabilistic reasoning abilities across age groups and within the youngest age group. Notably, Ruggeri et al (2018) only assessed children's ability to compare probabilities.…”
Section: Probabilistic Reasoning Abilities and Early Numerical Abilitiesmentioning
confidence: 97%
See 2 more Smart Citations